PENGEMBANGAN MEDIA PEMBELAJARAN DALAM BENTUK VIDEO TUTORIAL BILINGUAL UNTUK PEMBELAJARAN FISIKA SISWA SMA KELAS XI SEMESTER 1 - Rezi Marcelina (Universitas Negeri Padang, 2013)
Bilingual video tutorial media is an effort to create the concept of self-learning in students. For it has done research on the development of instructional media in the form of bilingual video tutorial for learning physics high school students of SMAN 3 Padang in class XI IPA 7. Type of research is research & development conducted through several steps. The first, bilingual video tutorial media validated by experts. Second, product revision, and the third is done product testing on high school students of class XI IPA 7. From the results, the average value of the validity of bilingual video tutorial media design for learning physics students was 87.17, the average value of the practicalities of media was 88.25%, and the value of the effectiveness of the use of bilingual video tutorial media that obtained from the the result of thitung of student's pre test and post test was 16.38. This proves that the bilingual video tutorial media is valid, practical, and effective as learning resources for students to create the concept of self-learning in students. Keywords: Learning Media, Tutorial Video, Bilingual, Physics Learning